2015
DOI: 10.1021/acs.analchem.5b03298
|View full text |Cite
|
Sign up to set email alerts
|

Cesium Speciation in Dust from Municipal Solid Waste and Sewage Sludge Incineration by Synchrotron Radiation Micro-X-ray Analysis

Abstract: The chemical behavior of Cs in waste incineration processes is important to consider when disposing of radionuclide-contaminated waste from the Fukushima Daiichi nuclear power plant accident in Japan. To determine the speciation of Cs, we attempted the direct speciation of trace amounts of stable Cs in the dust from municipal solid waste incineration (MSWI) and sewage sludge incineration (SSI) by micro-X-ray fluorescence (μ-XRF) and micro-X-ray absorption fine structure (μ-XAFS) at the SPring-8 facility. The μ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 23 publications
1
19
1
Order By: Relevance
“…Current knowledge on the behavior of r-Cs or stable Cs in MSWI and SSI is as follows: more than half of the r-Cs 9 and stable Cs 22 in MSW were distributed to fly ash (MSWI-FA) in stoker incineration plants. The chemical form of Cs in MSWI-FA was identified as mostly chlorides 9,10,12,16 or at least water-soluble forms. 13−16 According to the analyses of the residues of co-incineration of MSW and Cs 2 CO 3 reagent, 11,12 Cs in the MSW bottom ash (MSWI-BA) was mostly glassy materials or metal sulfides or crystalline aluminosilicates such as pollucite, except for the unchanged reagents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current knowledge on the behavior of r-Cs or stable Cs in MSWI and SSI is as follows: more than half of the r-Cs 9 and stable Cs 22 in MSW were distributed to fly ash (MSWI-FA) in stoker incineration plants. The chemical form of Cs in MSWI-FA was identified as mostly chlorides 9,10,12,16 or at least water-soluble forms. 13−16 According to the analyses of the residues of co-incineration of MSW and Cs 2 CO 3 reagent, 11,12 Cs in the MSW bottom ash (MSWI-BA) was mostly glassy materials or metal sulfides or crystalline aluminosilicates such as pollucite, except for the unchanged reagents.…”
Section: Introductionmentioning
confidence: 99%
“…9,13,14 In sewage sludge incineration (SSI) using a fluidized-bed incinerator, r-Cs in the SSI-fly ash (SSI-FA) was mostly water-insoluble. 13,14,17−21 The chemical forms of r-Cs in the SSI-FA have not yet been directly determined, but are suggested as aluminosilicate 10 or part of the oxides including iron. 19 Some studies have reported that in highly alkaline solution (pH > 12) 18 or in acidic solutions, 17,19 leachability of the r-Cs from the SSI-FA increased greatly.…”
Section: Introductionmentioning
confidence: 99%
“…Cs is known to be a volatile element [15]. In addition, the Cs present in BA and FA exists in different forms [11,[16][17][18]. This is because most r-Cs enters municipal solid waste (MSW) incineration facilities via vegetation and soil and is volatilized into a gaseous state during incineration, following which it migrates into the flue gas [19].…”
Section: Elemental Composition Of Ash Samplesmentioning
confidence: 99%
“…The r-Cs cools near the baghouse filter, which is controlled at a temperature of approximately 200 • C. The r-Cs then solidifies and concentrates in the FA. Therefore, Cs may exist in FA in the form of highly water-soluble CsCl [8,17,18], CsOH, and Cs 2 SO 4 [20,21].…”
Section: Elemental Composition Of Ash Samplesmentioning
confidence: 99%
See 1 more Smart Citation